Health Beneficial Aspect and Therapeutic Potential of Cirsimaritin in the Medicine for the Treatment of Human Health Complications - Patel, Dinesh K. (Current Bioactive Compounds, 2022)
Background: Herbal plants have been used in medicine for the treatment of numerous human health complications. Plant-derived products, including extract, botanicals, and preparations, have been used in medicine and other allied health sectors since a very early age and have been available in the market for several decades. Flavonoids have been a well-known class of phytochemicals in medicine due to their anti-oxidant, anti-cancer, anti-inflammatory, anti-bacterial and hepatoprotective potential. Methods: In order to know the medicinal importance and therapeutic benefit of cirsimaritin in medicine, in the present investigation, scientific research data have been collected and analyzed from various literature data sources, including Science Direct, Google, Google Scholar, PubMed, and Scopus. Detailed pharmacological activities of cirsimaritin have been analyzed to know the biological potential of cirsimaritin. However, for the standardization of plant material, numerous analytical techniques have been developed in the scientific field, and analytical data of cirsimaritin have been collected and analyzed in the present work. Results: Cirsimaritin, also called 4',5-dihydroxy-6,7-dimethoxyflavone, is a flavonoidal class phytochemical found to be present in the medicinal plant. It has been utilised in medicine to address a wide range of human health issues. Through the analysis of scientific data, it was found that cirsimaritin has numerous health beneficial aspects due to its vast pharmacological activities. Its medicinal importance is mainly due to its anti-oxidant, anti-bacterial, and anti-inflammatory activities. Further data analysis revealed the therapeutic effectiveness of cirsimaritin on breast cancer, gallbladder carcinoma, central nervous system disorders, diabetes mellitus, melanogenesis, immune responses, human erythrocytes, and respiratory burst. The importance of GC-MS, LC-MS, HSSPME, FTIR, ICP-OES, MS, NMR, LC/ESI-MS/MS, HPLC, reversed-phase HPLC, and TLC techniques for the analysis of cirsimaritin has been revealed. Conclusion: The biological importance of cirsimaritin for the treatment of human health complications was revealed; it could also be used for the development of effective medicine against human disorders.
Keywords: anti-inflammatory